The Federal Income Tax: Its Sources and Applications (Book). - Meyer, Philip E.; Yellin, William (The Accounting Review, 1982)
Reviews the book "The Federal Income Tax: Its Sources and Applications, 1982" by Clarence F. McCarthy, D. Larry Crumbley and P. Michael Davis.